A convenient one-pot synthesis, and characterisation of the ω-bromo-1-(4-cyanobiphenyl-4'-yl) alkanes (CBnBr). Issue 12 (26th September 2022) - Gibb, Calum J; Storey, John MD; Imrie, Corrie T
ABSTRACT: A convenient synthetic route based on a sodium-mediated aromatic cross-coupling reaction is described for the multi-gram preparation of the ω-bromo-1-(4-cyanobiphenyl-4'−yl) alkanes (CB n Br, n = 2–10). These materials are not only key intermediates in the synthesis of oligomers and polymers but also exhibit fascinating liquid crystal behaviour in their own right. Nematic behaviour is observed for n ⩾5, and the nematic-isotropic transition temperature, TNI, increases in essentially a linear manner on n . The properties of the ω-bromo-1-(4-cyanobiphenyl-4'−yloxy) alkanes (CBO n Br, n = 2–9) are also reported, and nematic behaviour is seen for n ⩾3. The values of TNI show a weak odd-even effect on n in which the odd members show the higher values. The sense of this alternation is opposite to that seen for the 4-alkyloxy-4'-cyanobiphenyls, and this is attributed to the steric bulk of the bromine atom. The absence of smectic behaviour for both the CB n Br and CBO n Br series is attributed largely to electrostatic interactions that would arise from the concentration of the bromine atoms at the layer interfaces in an interdigitated smectic phase. A comparison of a range of cyanobiphenyl-based materials containing a chain with a terminal polar or polarisable group suggests that their phase behaviour is governed largely by their average molecular shapes. GRAPHICAL ABSTRACT: uf0001